Intimate Partner Violence (IPV) - Associated Ophthalmologic Injuries among Women: A Systematic Review - Katherine Marl R. Ferrer, MD; Maria Donna D. Santiago, MD, MBA (Philippine Journal of Ophthalmology, 2025)
Objectives: This study aims to describe patterns of IPV-associated ophthalmic injuries among women: Specifically, it seeks to identify factors associated with ophthalmic injuries in women secondary to IPV, determine practices and/or protocols in identifying IPV-associated ophthalmic injuries, and to examine practices in referral to ancillary services for IPV survivors with such injuries.